How does future focus promote study engagement? A moderated mediation model of self‐esteem and dispositional awe. Issue 1 (24th October 2020) - Zhang, Furong; Feng, Shiting; Li, Jie
Abstract: Sufficient engagement in studying promotes students' academic performance and ability to compete in the job market. In this study, we explore the role of future focus and dispositional awe in stimulating college students' study engagement. To examine our hypotheses, we conducted a questionnaire survey with 237 students from a national college in China. The results indicate that future focus is positively related to study engagement and that self‐esteem mediates this relationship. Moreover, the mediating effect of self‐esteem is moderated by dispositional awe such that the mediation relationship is weaker when the level of awe is higher. Implications and directions for future research are discussed.